SELLING PRICE DETERMINATION MODEL WITH TIME DRIVEN ACTIVITY BASED COSTING METHOD AT UMKM ”SALE PISANG” IN BANYUWANGI REGENCY - Deddy Kurniawansyah (Universitas Airlangga, 2021)
The purpose of this study to examine (1) how the stages of the production process for “Sale Pisang Product’ that affects the determination of the selling price of Micro, Small, and Medium Enterprises in Banyuwangi? (2) How is the selling price computing model